2019
DOI: 10.1088/1755-1315/270/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Forest conversion into cacao agroforestry and cacao plantation change the diversity of arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhizal fungi (AMF), a plant root-fungus association, has been studied widely across different ecosystems. However, little information provided in tropical land use systems. Here, we studied the diversity of AMF in the forest, cacao agroforestry, and cacao plantation. A preliminary survey was done to estimate the AMF richness and diversity. This study reveals an interesting fundamental finding where AMF richness and diversity were significantly higher in the plantation compared to the natural ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…cultivation significantly affected the α-diversity of pine fungi, but not the community structure (bacteria, fungi). Land use conservation, such as forest conservation in the cacao agroforestry system, can significantly affect fungal diversity but not bacterial diversity ( Edy et al, 2019 ). Previous studies have shown that the effect of land conservation on fungi is mainly due to variations in soil organic matter content and plant root vigor ( Beule et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cultivation significantly affected the α-diversity of pine fungi, but not the community structure (bacteria, fungi). Land use conservation, such as forest conservation in the cacao agroforestry system, can significantly affect fungal diversity but not bacterial diversity ( Edy et al, 2019 ). Previous studies have shown that the effect of land conservation on fungi is mainly due to variations in soil organic matter content and plant root vigor ( Beule et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies have shown that agroforestry increases the diversity of moso bamboo endophytes and significantly alters their community composition ( Zhang H. Z. et al, 2019 ; Zhang X. et al, 2019 ). Similarly, studies have found that the richness and the colonization rate of arbuscular mycorrhizal fungi of crops increase under agroforestry management ( Sousa et al, 2013 ; Edy et al, 2019 ). In fact, the changes in endophytic bacteria in crops are closely related to soil microbiomes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the cocoa crops (forest, agroforestry, and plantation), AMF diversity and community structure are strongly influenced by vegetation and ecological conditions, with lower diversity in natural ecosystems than the plantation [ 98 ]. In early studies, a mixture of AMF species of Gigaspora spp.…”
Section: Preharvestmentioning
confidence: 99%
“…In a recent study on AMF on tree crops, , Edy et al (2019) and Famuwagun and Agele (2019) found that AMF from different origin can colonize cocoa and coffee and has the potential to improve their vegetative growth (stem diameter, plant height and leave area).…”
Section: Role Of Amf In Plants Under Water Stress (Drought) Conditionmentioning
confidence: 99%